2016
DOI: 10.1155/2016/3238909
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Physicochemical Characterization of Laccase fromGanoderma lucidum-CDBT1 Isolated from Its Native Habitat in Nepal

Abstract: At present, few organisms are known to and capable of naturally producing laccases and white rot fungi are one such group. In the present study, three fungal species, namely, Ganoderma lucidum-CDBT1, Ganoderma japonicum, and Lentinula edodes, isolated from their native habitat in Nepal were screened for laccase production, and G. lucidum-CDBT1 was found to express highest levels of enzyme (day 10 culture media showed 0.92 IU/mg total protein or 92 IU/mL laccase activity with ABTS as substrate). Lignin extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
4
18
0
Order By: Relevance
“…Also, by combining tamarind shell with ethanol (3%, v/v), CuSO 4 (0.4 mM), and gallic acid (1 mM) the value of 74.84 U/ml was achieved after 15 days, which was 416 times higher in comparison with the control . On the other hand, Shresta et al achieved 93 U/ml of laccase activity with a much lower CuSO 4 concentration of 30 μM, after 10 days of cultivation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, by combining tamarind shell with ethanol (3%, v/v), CuSO 4 (0.4 mM), and gallic acid (1 mM) the value of 74.84 U/ml was achieved after 15 days, which was 416 times higher in comparison with the control . On the other hand, Shresta et al achieved 93 U/ml of laccase activity with a much lower CuSO 4 concentration of 30 μM, after 10 days of cultivation.…”
Section: Discussionmentioning
confidence: 97%
“…Kraft lignin, also called alkali lignin, is largely produced by pulp and paper industry during the cooking process . Shrestha et al reported the potential of lignin isolated from rice for induction of laccase activity on G. lucidum. Sitarz et al evaluated the ability of G. lucidum , Polyporus brumalis , Polyporus ciliatus , and Trametes versicolor to grow on malt extract and minimal media containing alkali lignin and only G. lucidum showed the ability to grow on these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…B7 on guaiacol agar and α-napthol agar with dark brown and deep purplish colours around the colonies indicating laccase production. Several authors have reported the oxidation of ABTS, guaiacol and α-napthol by laccase-producing fungi to produce dark green, reddish brown and deep purplish halos respectively, around colonies on solid media incorporated with the indicators [11,38,40]. Isolates which did not show any colour change lacked laccase activity and were not considered for further work.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported the use of ABTS, guaiacol and α-naphthol in plate screening for visual identification of laccases [8]. Oxidation of guaiacol presents reddish brown colour, α-naphthol a deep purple colour, and 2, 2-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) a dark green halo around laccaseforming colonies on agar [11]. Most fungal laccases prefer ABTS as the ideal substrate [8].…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes catalyze the oxidation of various phenolic and nonphenolic compounds and complementarily reducing the molecular oxygen to water (Casciello et al, 2017). The enzymes from wood-rotting basidiomycetes possess significant interest because of their ability to utilize a wide spectrum of carbon sources, including intermediates of lignin degradation, phenols, and heterocyclic compounds (Shrestha et al, 2016).…”
Section: Issn: 2319-7706 Volume 7 Number 08 (2018)mentioning
confidence: 99%